Eudaimonism: Juxtaposition to the Concept of the Last Judgment on Matthew 25:31-46 - Alvyn Cesarianto Hendriks; Stimson Bernard Hutagalung; Jemmy Carter Najoan (Jurnal Jaffray, 2022)
The concept of “last judgment” means punishment for the wicked and reward for the righteous with the ultimate goal of human life. Philosophers’ theories sometimes contradict the contents of the Bible. Does eudaimonism go against the Bible or support each other? This study endeavours to cultivate a deeper insight into Aristotle’s happiness theory-eudaimonia juxtaposed with the pericope in Matthew about the final judgment. With a literature review approach, this qualitative method interpreted the narrative through several stages. Eudaimonia walks in rhythm with the concept of the final judgment in Matthew 25:31–46. Eudaimonia is about doing virtue as a self-maximizing potential to achieve the ultimate goal of human life, which is judged by reason as a demand of someone’s current situation with the assumption that leads to the truth. Matthew 25:31-46 reveals that the determination of “last judgment” is judged through practical religion by sharing Jesus’ friendship “today” through virtue with those who hunger and thirst for truth. Those who do it will receive the kingdom of God, and those who do not will be thrown into eternal fire.